Pengaruh Ketimpangan Pendapatan Dan Produktivitas Pertanian Terhadap Kemiskinan Di Provinsi Maluku - Lasaiba, Mohammad Amin (Jurnal Geografi, Lingkungan dan Kesehatan, 2023)
The issues of poverty, income inequality, and agricultural productivity are global problems that are still the main focus in many countries around the world. These three factors are interrelated and present complex and multidimensional challenges in sustainable economic development. This study aimed to examine the relationship between income inequality, agricultural productivity, and poverty in Maluku Province from 2018 to 2021. This study used a quantitative approach, and secondary data was taken from the Central Bureau of Statistics (BPS) using time series data. To test the hypothesis, the Ordinary Least Square (OLS) method was used in multiple regression analysis with SPSS 25.0 software. Before carrying out the regression analysis, the data is tested first with classical assumptions. The results showed no insignificant relationship between the poverty variable (Km) and income inequality variable (KP). There is a positive relationship between KP and changes in poverty, where the increase in KP is directly proportional to the increase in poverty and vice versa. However, there is no significant relationship between the variables Km and Agricultural Productivity (PP), so the effect of PP on Km is very small. The KP and PP variables have a relationship of 73.1% and an influence of 57.1% on the KM variable in Maluku Province in 2018-2021